DISRUPTIVE DEVELOPMENTS IN BIOMEDICAL APPLICATIONS - Shinde, Swati V.; Mahalle, Parikshit N.; Bendre, Varsha; Castillo, Oscar ([S.l.] : CRC PRESS, 2022)
This book covers advancements and future challenges in biomedical application development using disruptive technologies like artificial intelligence (AI), the Internet of Things (IoT), and signal processing. The book is divided into four main sections, namely, medical image processing using AI; IoT and biomedical devices; biomedical signal processing; and electronic health records, including advances in biomedical systems. It includes different case studies of biomedical applications using different AI algorithms related to diabetes, skin cancer, breast cancer, cervical cancer, and osteoarthritis. Features: Covers different technologies like AI, IoT, and signal processing in the context of biomedical applications. Reviews medical image analysis, disease detection, and prediction. Comprehends the advantage of recent technologies for medical record keeping through electronic health records (EHRs). Presents state-of-the-art research in the field of biomedical engineering using various physiological signals. Explores different bio sensors used in healthcare applications using IOT. This book is aimed at graduate students and researchers in AI, medical imaging, biomedical engineering, and IoT.
OCLC-licensed vendor bibliographic record.
Keywords: Biomedical engineering -- Technological innovations; COMPUTERS / Machine Theory; MATHEMATICS / Arithmetic; MEDICAL / Biotechnology